2020
DOI: 10.22515/relevance.v3i2.2956
|View full text |Cite
|
Sign up to set email alerts
|

Financial Distress Phenomenon of Non-financial Companies in Indonesia

Abstract: Penelitian ini bertujuan untuk memberikan gambaran mengenai kondisi financial distress pada masing-masing sektor perusahaan non keuangan di Indonesia periode 2014-2018. Sampel penelitian sebanyak 1.865 yang diperoleh melalui metode purposive sampling. Teknik analisis data menggunakan analisis statistik deskriptif. Hasil penelitian menunjukkan bahwa perusahaan di sektor infrastruktur, utilitas dan transportasi serta berbagai sektor industri mengalami financial distress. Perusahaan di sektor pertanian, sektor in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Ghasemzadeh et al (2021) found that EV significantly and negatively impact capital structure. Utami et al (2020) found a significant negative correlation between capital structure and EV in the utility, transportation, and infrastructure industries, but they are significantly and positively correlated in the mining sector. Lee and Manual (2019) revealed an opposite and strong relationship between FL and EV, external equity, and asset tangibility.…”
Section: Financial Distress and Capital Structurementioning
confidence: 89%
See 1 more Smart Citation
“…Ghasemzadeh et al (2021) found that EV significantly and negatively impact capital structure. Utami et al (2020) found a significant negative correlation between capital structure and EV in the utility, transportation, and infrastructure industries, but they are significantly and positively correlated in the mining sector. Lee and Manual (2019) revealed an opposite and strong relationship between FL and EV, external equity, and asset tangibility.…”
Section: Financial Distress and Capital Structurementioning
confidence: 89%
“…The study results suggest that PFTY and AS considerably and positively impact capital structure (Mujiatun et al, 2021). AS is inversely correlated with capital structure in the mining, food, and beverages industries; however, it shows a direct relationship in the agriculture sector (Utami et al, 2020). AS negatively affects the company's FL (Yunusa & Prasetyob, 2020).…”
Section: Asset Structure and Capital Structurementioning
confidence: 99%
“…Financial distress may be explicated as a state in which a commercial enterprise confronts challenges in fulfilling its monetary responsibilities, culminating in a reduction in the firm's worth and ultimately resulting in insolvency. As a consequence, the company is compelled to exit the market (Utami et al, 2020). In times of distress, such as the COVID-19 pandemic, enterprises with insufficient earnings and constrained monetary reserves must take diverse variables into consideration in order to endure.…”
Section: Introductionmentioning
confidence: 99%